Diversity Weeds on Plantation Coconut Palm (Elaeis Guineensis Jacq) in Institute Technology Palm Indonesia - Muhammad iqbal; Resty Fadhillah; Iqbal Bukhori; Ferdy Ikhwan; Poppy Fitria; Kurnainy Tohir; Habib Handoko; Guntoro Guntoro; Makhrani Sari; Maisarah Maisarah; Ingrid Ovie (International Journal of Educational Research Excellence (IJERE), 2024)
Weeds are annoying plants that can harm the main crop, weeds can grow quickly without being desired and also become obstacles to other activity mechanisms on the same land. The research was carried out in the practical garden of the Indonesian Palm Oil Technology Institute (ITSI), namely the Plantation campus, which has supporting facilities in the form of Oil palm plantation with an area of 6 hectares, this oil palm plantation (Elaeis guineensis Jacq.) has diverse plant vegetation with a height of 25 meters above sea level. This research focuses on exploring weed diversity in oil palm plantations at the Indonesian Palm Oil Technology Institute (Medan). By using field survey methods and vegetation analysis, the data is presented in qualitative descriptive form. This research reveals the types and distribution of weeds present, providing in-depth insight into the diversity of oil palm plantation ecosystems. The findings of this study show variations in weed vegetation and types that influence ecosystem balance. This research provides an important basis for further understanding of weed dynamics in oil palm plantations, creating a foundation for the development of more appropriate and sustainable management strategies.